Collusion of operators in wireless spectrum markets - (:unkn) unknown (My University, 2012)
The liberalization of wireless spectrum markets has been envisioned as a method for improving mobile communication services and accommodating the increasing traffic volumes of wireless users. It has been assumed that competition among operators will foster optimal utilization of wireless spectrum and ensure the provision of cost-efficient wireless services to users. However, spectrum markets often function inefficiently due to collusion of the operators. Although it is illegal and detrimental to users, such phenomena are often observed in real life as, for example, in the form of implicit price fixing. This results in a de-facto monopoly in the spectrum market to the detriment of the users. In this paper, we consider a general wireless spectrum market where a set of operators sell bandwidth to a large population of users. We use an evolutionary game model to capture the user dynamics in the presence of limited market information and analyze the interaction of the operators using coalitional game theory. We define a partition formation game in order to rigorously study the conditions that render the grand coalition (emergence of monopoly) stable under various stability notions. The results obtained provide a foundation for effective measures against operator collusion by altering the underlying motivations rather than fighting against the symptoms through law enforcement. © 2012 IFIP.
Keywords: Coalitional Game Theory; Collusion; Evolutionary Game Theory; Pricing; Resource Allocation